Rethinking rewritten scriptur e composition and exegesis in the 4Q reworked Pentateuch manuscripts - Zahn, Molly M. 1979- (Studies on the Texts of the Desert of Judah, 2011)
The Qumran discoveries have demonstrated that much of the earliest interpretation of Hebrew Scripture was accomplished through rewriting: production of revised editions of biblical books, or composition of new works drawing heavily upon Scripture for their organization and content. This study advances our understanding of the nature and purpose of such rewriting of Scripture by examining the compositional methods and interpretive goals of the five Reworked Pentateuch manuscripts from Qumran Cave 4 (4Q158, 364-367). This analysis, along with a comparison of the 4QReworked Pentateuch manuscripts to the Samaritan Pentateuch and the Temple Scroll, provides a clearer picture of how early Jewish communities read, transmitted, and transformed their sacred textual traditions.